Trade in War's Darkest Hour: Churchill and Roosevelt's Daring 1941 Atlantic Meeting that Linked Global Economic Cooperation to Lasting Peace and Security - Nottage, Hunter (Victoria University of Wellington Law Review, 2018)
A single page of text from the 1941 Atlantic Charter is a powerful reminder that the desire for peace and security drove the creation of today's global economic system. The global rules that underpin our multilateral economic system were a direct reaction to the Second World War and desire for it never to repeat.